STRATEGIC LEADERSHIP IN THE DEFENSE DIPLOMACY AND THE MODERNIZATION OF THE INDONESIAN MILITARY’S MAIN EQUIPMENT AND WEAPON SYSTEMS IN THE PERIOD OF 2019–2021 - Dave Akbarshah Fikarno Laksono; Muhammad Harry Riana Nugraha (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2022)
Strategic leadership of the Indonesian Ministry of Defense through its main competencies, namely conceptual, interpersonal, and technical, becomes an effective instrument in implementing defense diplomacy policies for the modernization of the Military's Main Equipment and Weapon Systems (Alat Utama Sistem Persenjataan or Alutsista). This study aims to analyze the strategic leadership of the Minister of Defense of the Republic of Indonesia through the use of defense diplomacy to modernize defense equipment. This study uses a qualitative method with a literature study approach. The results showed that the ability of the strategic leader is categorized into 3 (three) main competencies, namely: (1) Communication, i.e. a leader is expected to be able to express what is felt and what needs to be done; (2) Negotiation, is the appearance of communication conducted against opponents or outsiders to achieve the goal; and (3) Competence, is a leader must have competence; Conceptual, technical, and interpersonal. In terms of projections of the development and modernization of the defense industry, it will gradually begin to be achieved with a gradual implementation mechanism. Thus, policy measures and the reach of Minimum Essentials Forces (MEF) in 2024 are fulfilled simultaneously.